Purity of islet preparations and 5‐year metabolic outcome of allogenic islet transplantation. Issue 4 (11th November 2017) - Benomar, K.; Chetboun, M.; Espiard, S.; Jannin, A.; Le Mapihan, K.; Gmyr, V.; Caiazzo, R.; Torres, F.; Raverdy, V.; Bonner, C.; D'Herbomez, M.; Pigny, P.; et al.
Abstract : In allogenic islet transplantation (IT), high purity of islet preparations and low contamination by nonislet cells are generally favored. The aim of the present study was to analyze the relation between the purity of transplanted preparations and graft function during 5 years post‐IT. Twenty‐four patients with type 1 diabetes, followed for 5 years after IT, were enrolled. Metabolic parameters and daily insulin requirements were compared between patients who received islet preparations with a mean purity <50% (LOW purity) or ≥50% (HIGH purity). We also analyzed blood levels of carbohydrate antigen 19‐9 (CA 19‐9)—a biomarker of pancreatic ductal cells—and glucagon, before and after IT. At 5 years, mean hemoglobin A1c (HbA1c levels) ( P = .01) and daily insulin requirements ( P = .03) were lower in the LOW purity group. Insulin independence was more frequent in the LOW purity group ( P < .05). CA19‐9 and glucagon levels increased post‐IT ( P < .0001) and were inversely correlated with the degree of purity. Overall, our results suggest that nonislet cells have a beneficial effect on long‐term islet graft function, possibly through ductal‐to‐endocrine cell differentiation. ClinicalTrial.gov NCT00446264 and NCT01123187. Abstract : Five years after islet allotransplantation for type 1 diabetes, patients who receive a low purity islet preparation have better metabolic results compared to those who receive a high purity preparation, suggesting that non‐islet cells have a beneficial effect on long‐term islet graft function.